2022
DOI: 10.1177/03009858221120008
|View full text |Cite
|
Sign up to set email alerts
|

Fetoplacental pathology of equine abortion, premature birth, and neonatal loss due to Chlamydia psittaci

Abstract: This report describes the fetoplacental pathology of Chlamydia psittaci-associated abortion, premature birth, and neonatal loss in 46 of 442 equine abortion investigations between 2015 and 2019. Seven abortions, 26 premature births, and 13 neonatal deaths with positive C. psittaci polymerase chain reaction (PCR) were evaluated. In 83% of cases (38/46), C. psittaci infection was considered as the primary cause of loss based on quantitative PCR (qPCR) confirmation, pathological findings, and exclusion of other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…24 Both studies also reported PCR-positive cases with suppurative placentitis. 6,24 We identified 6 cases of placentitis in the PCRpositive group; 5 cases were identified as suppurative placentitis, and 1 was identified as mild lymphoplasmacytic placentitis. Suppurative placentitis was more common in our cases than in the reported equine studies of C. psittaci; however, suppurative placentitis is common in sheep with C. abortus abortion.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…24 Both studies also reported PCR-positive cases with suppurative placentitis. 6,24 We identified 6 cases of placentitis in the PCRpositive group; 5 cases were identified as suppurative placentitis, and 1 was identified as mild lymphoplasmacytic placentitis. Suppurative placentitis was more common in our cases than in the reported equine studies of C. psittaci; however, suppurative placentitis is common in sheep with C. abortus abortion.…”
Section: Discussionmentioning
confidence: 96%
“…26 The combined effects of these outcomes reduce fetoplacental exchange and ultimately cause abortion. 26 Placentitis, vasculitis, and rare thrombosis, similar to ovine cases of C. abortus, were reported in cases of C. psittaci equine abortions in Australia 6 ; the authors identified a characteristic lymphohistiocytic placentitis. 6 Similar findings were reported in C. psittaci abortions in Hungary in 2005.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this case, a monoclonal antibody targeting the chlamydial lipopolysaccharide was used to confirm that Chlamydia was associated with brain lesions using previously established methods. 8,15 IHC involves the specific immunolabelling of bacterial antigens within affected tissues followed by colorimetric detection of those antibodies using a chemical substrate. IHC has the advantage of co-localising an organism of interest within histological lesions and, therefore, is a powerful diagnostic tool for confirmation that the agent is responsible for the observed pathology.…”
Section: Discussionmentioning
confidence: 99%
“…IHC is another method that can be used for the diagnosis of chlamydial infections. In this case, a monoclonal antibody targeting the chlamydial lipopolysaccharide was used to confirm that Chlamydia was associated with brain lesions using previously established methods 8,15 . IHC involves the specific immunolabelling of bacterial antigens within affected tissues followed by colorimetric detection of those antibodies using a chemical substrate.…”
Section: Discussionmentioning
confidence: 99%